Disturbing figures: allusion and dismantling of metaphors in two stories by Antonio Di Benedetto - Colman Serra, Rocio (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
The Argentine writer Antonio Di Benedetto entered the literary circuit with the publication of Mundo animal in 1956, that is, within the framework of a key period in the history of literature in that country, fundamentally for productions that, as is the case of these stories, align within the universe of Fantasy literature. These are texts in which a deliberate search for ambiguity at a linguistic level is observed, which will be central to their entire narrative. In addition, these are writing practices that take into consideration plurivocity, the complexity that tropes and figures entail, which correspond to non-habitual signifiers, meanings or signs, that is, different from their counterpart in ordinary language. In this article we propose a textual analysis to diagram what we will call here the “Di Benedetto method”, associated with Fantasy. These are stories in which the coexistence between the different orders of what is presented as “normal” and “abnormal” in the text (Barrenechea) almost always begins through the combination of two operations: the introduction of doubt, level of discourse and work on allusion, metaphor and simile at the level of tropes and figures